Hubungan Komunikasi PembangunanProgram BKKBN Sukoharjo dengan Keputusan Penundaan Pernikahan Usia Dini Pada remaja di Kecamatan Gatak - Pertiwi, Santi, Agus Triyono, M.Si (2016)
Abstract Adolescents are the one who often experience problem, one ofthem is the high number of early marriage. It became a job that must be resolved by the government. Marrige age rejuvenation program is one program of BKKBN Sukoharjo, addressed to teenagers in the district Gatak and unmarried through preferences will be expected to with socialization, counseling, paphlets and billboards. Program marrige age rejuvenation of BKKBN preferences will be expectedto increasw the age of marriage adolescents in Gatak. The objectives of this research are to relationship between program BKKBN Sukoharjo (X) with decision dely early marriage among adolescents in Gatak (Y). This research used development communication proman and health promotion. This type of research quantitative method used was survey method. In this study uses a questionnaire in the data collection techniques. Location of this research is in Gatak. Hypotheses test using path analysiswith SPSS software. Research sample is tenagers between 15 to 19 years old, unmarried (n=100). Data analysis tecniques used in the study is a simple linier regression analysis. The result showed both variables are variables program BKKBN Sukoharjo (x) with a decision variable delay early marriage (Y) positively associated low. Based on the results of the test and simple linear regression, and regresion obtaineda costant value and variable delay earky marriageat 43,58. While the regression coefficient of variable delay early marriage at 42,76. This mean showing the relationship between the variables X and Y with a degree of positive relationships with low levels. Based on the results of product moment coefficient, obtained value of 0,283>0,195. Therefore, it can be concluded that Ho was rejected and Ha accepted.